2012
DOI: 10.1371/journal.pone.0049283
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of GTF2IRD1 Regulates Protein Partner Interactions and Ubiquitin-Mediated Degradation

Abstract: GTF2IRD1 is one of the genes implicated in Williams-Beuren syndrome, a disease caused by haploinsufficiency of certain dosage-sensitive genes within a hemizygous microdeletion of chromosome 7. GTF2IRD1 is a prime candidate for some of the major features of the disease, presumably caused by abnormally reduced abundance of this putative transcriptional repressor protein. GTF2IRD1 has been shown to interact with the E3 SUMO ligase PIASxβ, but the significance of this relationship is largely unexplored. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Since these original studies, a vast variety of proteins have been identified to be SUMO targets. SUMOylation regulates protein stability [154], protein-protein interactions [155] and subcellular localization [156], thereby impacting nearly all processes in the cell. The SUMOylation process is energy dependent similar to the ubiquitination process and involves three classes of enzymes, E1, E2 and E3.…”
Section: Sumoylationmentioning
confidence: 99%
“…Since these original studies, a vast variety of proteins have been identified to be SUMO targets. SUMOylation regulates protein stability [154], protein-protein interactions [155] and subcellular localization [156], thereby impacting nearly all processes in the cell. The SUMOylation process is energy dependent similar to the ubiquitination process and involves three classes of enzymes, E1, E2 and E3.…”
Section: Sumoylationmentioning
confidence: 99%
“…This supports the role of GTF2IRD1 in regulating chromatin by transcriptionally controlling other chromatin modifiers. These data, along with the localization pattern of GTF2IRD1 in the nucleus and its direct association with other chromatin modifiers such as ZMYM5 (18, 39), suggests that GTF2IRD1 can exert its regulation of chromatin at several different levels of biological organization. Motif enrichment analysis of GTF2IRD1 peaks indicated that CTCF cobind with GTF2IRD1.…”
Section: Discussionmentioning
confidence: 74%
“…While some GTF2IRD1 protein binding partners have been reported (Tussie-Luna et al 2002;Widagdo et al 2012) this area is unexplored and we therefore set out to address this need using a comprehensive screening approach.…”
Section: Endogenous Gtf2ird1 Is Found In Close Proximity To Elements mentioning
confidence: 99%
“…Five of these clones were not pursued beyond sequence identification as they were known to be solely cytoplasmic, extracellular or cell membrane localized and were less likely to be of biological relevance. Two of the proteins have been described previously as interacting nuclear partners (TussieLuna et al 2002;Widagdo et al 2012). Of the remaining 33 proteins, 26 either shuttle into the nucleus or are primarily located in the nucleus according to known functions or predictions summarized in the subcellular localization database, COMPARTMENTS (Binder et al 2014).…”
Section: Yeast Two-hybrid Library Screening For Novel Gtf2ird1 Interamentioning
confidence: 99%
See 1 more Smart Citation